Critical steps in the path to using cessation pharmacotherapy following hospital-initiated tobacco treatment - Edward P. Liebmann; Taneisha S. Scheuermann; Babalola Faseru; Kimber P. Richter (BMC, 2019)
Abstract Background Hospital-initiated smoking cessation interventions utilizing pharmacotherapy increase post-discharge quit rates. Use of smoking cessation medications following discharge may further increase quit rates. This study aims to identify individual, smoking-related and hospitalization-related predictors of engagement in three different steps in the smoking cessation pharmacotherapy utilization process: 1) receiving medications as inpatient, 2) being discharged with a prescription and 3) using medications at 1-month post-hospitalization, while accounting for associations between these steps. Methods Study data come from a clinical trial (N = 1054) of hospitalized smokers interested in quitting who were randomized to recieve referral to a quitline via either warm handoff or fax. Variables were from the electronic health record, the state tobacco quitline, and participant self-report. Relationships among the predictors and the steps in cessation medication utilization were assessed using bivariate analyses and multivariable path analysis. Results Twenty-eight percent of patients reported using medication at 1-month post-discharge. Receipt of smoking cessation medications while hospitalized (OR = 2.09, 95%CI [1.39, 3.15], p < .001) and discharge with a script (OR = 4.88, 95%CI [3.34, 7.13], p < .001) were independently associated with medication use at 1-month post-hospitalization. The path analysis also revealed that the likelihood of being discharged with a script was strongly influenced by receipt of medication as an inpatient (OR = 6.61, 95%CI [4.66, 9.38], p < .001). A number of other treatment- and individual-level factors were associated with medication use in the hospital, receipt of a script, and use post-discharge. Conclusions To encourage post-discharge smoking cessation medication use, concerted effort should be made to engage smokers in tobacco treatment while in hospital. The individual and hospital-level factors associated with each step in the medication utilization process provide good potential targets for future implementation research to optimize treatment delivery and outcomes. Trial registration Number: NCT01305928. Date registered: February 24, 2011.